Food environment research in Vietnam: A desk review - Clarke, Rebecca Namara; Nabuuma, Deborah; Gebru, Mestawet; Termote, Celine (2025)
Food environments shape dietary behaviors and nutrition outcomes, acting as the space where people engage with and navigate the broader food system [1]. In Vietnam, rapid economic growth, urbanization, and food system transformation have led to changes in food retail structures, market organization, and dietary patterns. As poor-quality diets continue to contribute significantly to the global burden of disease, understanding the determinants within food environments that constrain or enable access to diverse, nutritious, and safe diets remain essential for policy and programming aimed at improving diet quality and nutrition outcomes. While market-based food environments tend to dominate existing discussions, research increasingly recognizes the importance of wild and cultivated, institutional, and kin- or community-based food environments as critical spaces where food sourcing and consumption decisions occur [2]. This research brief provides an overview of Vietnam’s food environment, drawing on a scoping review of published evidence. Specifically, the brief synthesizes methodological approaches and considers how they shape insights into consumer food environments, it maps the types of food environments, dimensions, and individual factors that have been previously examined, and identifies the contexts in which food environments have been studied and the populations most frequently engaged. The review further highlights key findings on food environment characteristics, outlining barriers and enablers to healthy diets, with particular focus on fruit and vegetable consumption. The brief also summarizes food environment-related interventions assessed and reflects on evidence regarding their effectiveness and scalability.